Agricultural conversion without external water and nutrient inputs reduces terrestrial vegetation productivity. Issue 2 (16th January 2014) - Smith, W. Kolby; Cleveland, Cory C.; Reed, Sasha C.; Running, Steven W.
Abstract Driven by global population and standard of living increases, humanity co‐opts a growing share of the planet's natural resources resulting in many well‐known environmental trade‐offs. In this study, we explored the impact of agriculture on a resource fundamental to life on Earth: terrestrial vegetation growth (net primary production; NPP). We demonstrate that agricultural conversion has reduced terrestrial NPP by ~7.0%. Increases in NPP due to agricultural conversion were observed only in areas receiving external inputs (i.e., irrigation and/or fertilization). NPP reductions were found for ~88% of agricultural lands, with the largest reductions observed in areas formerly occupied by tropical forests and savannas (~71% and ~66% reductions, respectively). Without policies that explicitly consider the impact of agricultural conversion on primary production, future demand‐driven increases in agricultural output will likely continue to drive net declines in global terrestrial productivity, with potential detrimental consequences for net ecosystem carbon storage and subsequent climate warming.